Evaluation of Intraocular Pressure in Thyroid-associated Orbitopathy - Gautam Adhikari, Pragati; Shrestha, Gulshan Bahadur (Journal of Nepal Health Research Council, 2022)
Background: Elevated intraocular pressure in thyroid associated orbitopathy may lead to development of secondary glaucoma in them. This study evaluated IOP in primary gaze correlation with clinical activity score in them.Methods: A cross-sectional study was conducted from November 2020 to October 2021.Information on age, gender, thyroid function test, intraocular pressure, cup-disc ratio and clinical activity score were recorded. Purposive sampling was done. Statistical analysis was done using Statistical Package for Social Sciences version 21.Results: Total of 74 thyroid dysfunction patients was included in the study. There were14.86% patients with raised intraocular pressure. The mean intraocular pressure in hyperthyroidism was 15.4 ± 1.92 mm Hg and 15.48 ± 2.11mm Hg on right and left eyes respectively and in hypothyroidism, it was 15.08 ± 2.7mmHg and 15.12 ± 3.02 mmHg on right and left eyes respectively. The mean clinical activity score was 1.06 ± 1.23 mmHg. The mean intraocular pressure in eyes in active stage (n=9) was 16.3 ± 3.4 mm Hg, which was not significantly different from the mean intraocular pressure of 15 ± 2.4 mm Hg in inactive eyes (64), p= 0.1. Clinical activity score showed a significant correlation (p=0.03) with intraocular pressure in right eyes whereas it showed no significant correlation with intraocular pressure in left eyes (p=0.37).Conclusions: In this study elevated intraocular pressure occurred in about 1 in 7 thyroid associated orbitopathy. It also had positive correlation with clinically activity score in right eyes. Regular intraocular pressure measurement should be done in thyroid associated orbitopathy to prevent intraocular morbidity.Keywords: Clinical activity score; intraocular pressure; orbitopathy; thyroid dysfunction.